2022
DOI: 10.21037/atm-22-2179
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic polymorphisms in unexplained recurrent spontaneous abortion based on whole exome sequencing

Abstract: Background: The precise etiology of approximately 50% of patients with recurrent spontaneous abortion (RSA) is unclear, known as unexplained recurrent spontaneous abortion (URSA). This study identified the genetic polymorphisms in patients with URSA.Methods: Genomic DNA was extracted from 30 couples with URSA and 9 couples with normal reproductive history for whole exome sequencing. Variations in annotation, filtering, and prediction of harmfulness and pathogenicity were examined. Furthermore, predictions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…In the first study, a match between rare copy number variations (CNV) in the ZIC5 gene and abnormal voluntary movement was identified in a mouse model of global developmental disorder [29]. In the second study, a Whole Exome Sequencing (WES) study was performed in couples with recurrent miscarriages, and missense, non-pathogenic changes were detected in the ZIC2 and ZIC5 genes in the patient group [30]. In the present study, the polymorphic variant appears to be protective for NTD.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, a match between rare copy number variations (CNV) in the ZIC5 gene and abnormal voluntary movement was identified in a mouse model of global developmental disorder [29]. In the second study, a Whole Exome Sequencing (WES) study was performed in couples with recurrent miscarriages, and missense, non-pathogenic changes were detected in the ZIC2 and ZIC5 genes in the patient group [30]. In the present study, the polymorphic variant appears to be protective for NTD.…”
Section: Discussionmentioning
confidence: 99%
“…Next generation sequencing (NGS), particularly the exome sequencing, has been extensively used to identify the gene variants underlying human genetic diseases. To date, fourteen studies have been reported to perform exome sequencing for identification of potential genes and genetic mutations contributing to RPL ( Table S1 and S2 [ 128 ], [ 129 ], [ 130 ], [ 131 ], [ 132 ], [ 133 ], [ 134 ], [ 135 ], [ 136 ], [ 137 ], [ 138 ], [ 139 ], [ 140 ], [ 141 ]). Most of these studies focus on the discovery of RPL-associated mutations in women patients, and a total of 66 candidate maternal genes and 12 paternal genes have been reported to be associated with RPL ( Table 1 ).…”
Section: Maternal and Paternal Genetic Factors Account For Rplmentioning
confidence: 99%
“…Tian et al, 2018) (J. Wang et al, 2021). Additionally, research indicates that polymorphisms in many genes, including those that control cell migration like IGF-2 and PAI-1, are linked to recurrent miscarriage (Shi et al, 2017) (Mou et al, 2022). As a result, a study into the relationships between genetic polymorphisms that govern the migration of cells, invading cells, and recurrent abortions may help us better understand the etiology of recurrent miscarriage.…”
Section: Introductionmentioning
confidence: 99%